A hybrid influence method based on information entropy to identify the key nodes - Zhong, Linfeng; Gao, Xiangying; Zhao, Liang; Zhang, Lei; Chen, Pengfei; Yang, Hao; Huang, Jin; Pan, Weijun (Frontiers in Physics, 2023)
Identifying the key nodes in complicated networks is an essential topic. A number of methods have been developed in recent years to solve this issue more effectively. Multi-attribute ranking is a widely used and efficient method to increase the accuracy of identifying the key nodes.Using k-shell iteration information and propagation threshold differences, we thoroughly analyze the node's position attribute as well as the propagation attribute to offer a hybrid influence method based on information entropy. The two attributes will be weighted using the information entropy weighting method, and then the nodes' influence ranking will be calculated. Correlation experiments in nine different networks were carried out based on the Susceptible Infection Recovery (SIR) model. Among these, we use the imprecision function, Kendall's correlation coefficient, and the complementary cumulative distribution function to validate the suggested method. The experimental results demonstrate that our suggested method outperforms previous node ranking methods in terms of monotonicity, relevance, and accuracy, and performs well to achieve a more accurate ranking of nodes in the network.